The influence of non-domestic factors on elite sport development and anti-doping policy: the cases of Japan and the UK/England - Yamamoto, M. Y.-Y. (2009)
The aim of this thesis is to examine the extent to which selected aspects of sport policy in Japan and also UK/England are influenced by international forces. The objectives which underpin the research aim are to analyse the characteristics of the domestic policy areas and identify the varying degree of impact of external influences on domestic sport policy. The thesis examines the interactions between domestic and international factors that shape elite sport policy and anti-doping policy and seeks to identify how domestic institutional values and ideas have been shaped by global influences. Importantly, by analysing the nature and mechanisms of global influence that are manifest at the domestic level, it is intended to identify varying degree of impact external to national policy. To achieve the above objectives, a qualitative methodology and related documentary research methods are adopted in the empirical investigations. Policy document analysis and semi-structured interviews are employed. The cases of UK (or England where appropriate) are introduced in order to generate a deeper understanding of the development of Japanese elite sport and anti-doping policy. The thesis draws on a range of theoretical frameworks, including international relations theory, international regime theory and globalisation, to analyse the empirical data. By adopting these theoretical frameworks, it is aimed to identify the possible characteristics of international policy regimes in the policy areas of elite sport and anti-doping. With regard to the development of elite sport policy, the general observation is that a myriad of intermingling pressures have been stimulated by processes of globalisation. The empirical study shows that the realist notion of international relations has the potential to illustrate the capacity of states over the development of elite sport policy. The recent development of global anti-doping provisions and the internationally-agreed principles and values in 'play fair' have influenced domestic policy through a complex series of interactions between global and domestic forces. A policy regime is discernible in anti-doping policy whose effectiveness is based on the regulation of the policy area of anti-doping. However, it is evident that the outcome of interactions between the domestic and the global illustrates the differences between Japan and the UK. It is possible to identify an element of 'coercion' in the current global anti-doping arrangements where sanctions and monitoring are undertaken by the World Anti-Doping Agency. There is a different degree of 'calculated' national interest in benefits and costs associated with global policy principles, norms and compliance. As for the case of elite sport policy development, interactions between domestic and non-domestic factors can be explained better with the application of globalisation concepts. Despite the states retaining substantial capacity and autonomy over many aspects of elite sport policy acting out of their self-interests, the capacity of globalisation to 'reach in' to the domestic policy process becomes apparent with different degrees of the 'enabling' impacts of globalisation between Japan and British contexts. This thesis demonstrates the advantages of using a broad international relations framework to demonstrate the applicability of theoretical frameworks of international relations, international policy regimes and globalisation to the analysis of the interaction between global and national/local sport policies. With the objective to fill the gaps in knowledge, the thesis highlights the substantial contributions, in particular, to understanding the development of sport policy in Japan and the processes of global pressure manifest at domestic level as constraining and enabling factors, while future research will possibly be required to refine theoretical applications to the field of sport policy and advance the area of comparative study.